Sustained complete response of advanced hepatocellular carcinoma with metronomic capecitabine: a report of three cases. Issue 1 (26th June 2018) - Brandi, Giovanni; Venturi, Michela; De Lorenzo, Stefania; Garuti, Francesca; Frega, Giorgio; Palloni, Andrea; Garajovà, Ingrid; Abbati, Francesca; Saccoccio, Gioconda; Golfieri, Rita; Pantaleo, Maria Abbondanza; Barbera, Maria Aurelia
Abstract: Background: Hepatocellular carcinoma (HCC) is one of the most frequent causes of cancer‐related death. Sorafenib, a multitarget angiogenesis inhibitor, is an approved frontline treatment for advanced HCC in Western countries, although a complete response (CR) to treatment is infrequently reported. Capecitabine, an oral fluoropyrimidine, has been shown to be effect in both treatment‐naïve patients and those previously treated with sorafenib. To date, however, only one case of sustained CR to metronomic capecitabine has been reported. Case presentation: We describe three cases of advanced HCC treated with metronomic capecitabine where a CR was obtained. In the first case, capecitabine was administered as first line therapy; in the second case, capecitabine was used after intolerance to sorafenib; while in the third case, capecitabine was administered after sorafenib failure. Conclusion: Capecitabine is a potentially important treatment option for patients with advanced HCC and may even represent a cure in certain cases.